Role of Family Business in India : Challenges & Suggestive Approaches: Exploring the Challenges and Opportunities of Family Businesses in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
A family business is an enterprise in which two or more members collaborate , managed andcontrolled the family business. India have glorified and enrich history of family business. Over the year,family organizations have faced many barriers, and the position of administration has shifted frominternal leadership to the collaboration of outer family business leaders. Reliance, MDH, Tata Birla, JIO,Infosys Limited etc. family businesses are the best example of successful enterprises over the more thanthree generations. But still family businesses are facing major problems and challenges like conflictionbetween family members, lack of succession planning, Lack of training, Communication gaps, No writtendocuments, sibling rivalry etc. If new generation respects old generation and considers their experienceand at the same time old generation should consider creativity of new generation, then familybusinesses will have more opportunities in Indian economy. The paper starts with a brief on the past andessence of family business in India, accompanied by the problems of external business leaders and theirincorporation. We would also discuss what makes effective and golden rules methods needed to savethe business in the family.Existing literature on family businesses brings out their significance globally.The prevalence of family businesses is a phenomenon that is universal and found in most countriesworldwide, although their relative impact on economies does vary. This article reviews papers in theaccounting and finance literature on family businesses around the world and shows that the involvementof family members in the business may have a positive, negative or no impact on its financialperformance. In the Indian context, the literature review indicates that India‟s rich and ancient historyseems to be interrelated with the family-run businesses as the principal means of business organization.The paper gives a glimpse of the status of family businesses in India since independence and thedistinct characteristics of Indian family businesses.